VISITORS SATISFACTION STUDY OF JOLLONG PATI AGRITOURISM IN TERMS OF SERVQUAL DIMENSIONS - Remaylian Nurani; Wiludjeng Roessali; Titik Ekowati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
Consumer satisfaction is an indicator of the sustainability of a business. A good visitor rating on the agro-tourism company will affect the sustainability of the company. Visitors will give a good rating when the performance of the services provided is also good. This study aimed to analyze the performance of Jollong Agro-tourism service quality attributes (servqual dimension) and to measure the satisfaction of Jollong Agro-tourism visitors from the service quality aspect. The research data collection was done by survey method. Data collection was conducted from December 2019 – to January 2020 at Jollong Agro-tourism, located in Sitiluhur Village, Gembong District, Pati Regency. The research location was determined purposively because of the conditions and natural beauty in Jollong Agro-tourism's potential to be developed. The research samples are visitors who were selected accidentally; 100 visitors were taken by the quota method. The analytical techniques used are Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The analysis results showed an average suitability score (Tki) measured by IPA of 86.70%, meaning that there was still a performance that did not fulfill the visitor expectations so needed to be repaired; the visitor satisfaction index of Jollong Agro-tourism measured by CSI of 67.20%, so it is classified as satisfied. The recommendations of this study are improving the performances of priority attributes by rebuilding toilet facilities, repairing the damaged facilities/vehicles, providing free wifi service, providing trash bins with a clue board, providing health facilities, and making the connecting access between Jollong and Jurang area.